2016
DOI: 10.3758/s13423-016-1063-0
|View full text |Cite
|
Sign up to set email alerts
|

Contextual cuing as a form of nonconscious learning: Theoretical and empirical analysis in large and very large samples

Abstract: Numerous studies have demonstrated that associative learning can affect visual cognition. In one such effect, search times for a target hidden among similar distractors are faster for repeated search configurations compared with novel configurations. This contextual cuing effect is particularly interesting, because researchers routinely have failed to find evidence of recognition of the repeated configurations, concluding that the effect is a form of nonconscious learning. Vadillo, Konstantinidis, and Shanks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 25 publications
5
94
0
Order By: Relevance
“…Previous research showed that while contextual cueing is of high capacity and is considered a genuine form of effortless, nonconscious, learning (Colagiuri & Livesey, 2016), the memory underlying the cueing effect is quite resistant to forming an association between a new target location and an existing distractor representation. This 'lack of adaptation' was replicated in Experiment 1 and in various other experiments conducted in the course of our research (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that while contextual cueing is of high capacity and is considered a genuine form of effortless, nonconscious, learning (Colagiuri & Livesey, 2016), the memory underlying the cueing effect is quite resistant to forming an association between a new target location and an existing distractor representation. This 'lack of adaptation' was replicated in Experiment 1 and in various other experiments conducted in the course of our research (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the traditional sources of evidence have failed to convince all theorists that it is necessary to posit association formation as being mechanistically distinct from inferential reasoning or higher order cognition in general. For instance, the notion that associative learning can occur in the absence of awareness is still as contentious as ever (see Goujon et al, 2015; Colagiuri and Livesey, 2016; Vadillo et al, 2016 for a recent iteration of this debate concerning implicit learning in visual search). Nevertheless, a number of results (e.g., Morís et al, 2014; Perruchet, 2015; Cobos et al, 2016) suggest that associative learning mechanisms are separable from other cognitive sources of expectation in at least some circumstances and could represent the operation of an independent system.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of such results, it has been proposed that CC is produced by automatic implicit (unconscious) learning of the repeated configurations (refs 4 and 5; but see ref. 6).…”
mentioning
confidence: 99%